2019
DOI: 10.31616/asj.2018.0125
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Topical Application of Tranexamic Acid in Patients with Thoracolumbar Spine Trauma Undergoing Long-Segment Instrumented Posterior Spinal Fusion

Abstract: Study DesignProspective, randomized controlled trial.PurposeTo evaluate the effect of topically applied tranexamic acid (TXA) on postoperative blood loss of neurologically intact patients with thoracolumbar spine trauma.Overview of LiteratureFew articles exist regarding the use of topical TXA for postoperative bleeding and blood transfusion in spinal surgery.MethodsA total of 57 patients were operated on with long-segment instrumented fusion without decompression. In 29 patients, a solution containing 1 g of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Table (1) shows that the female (63.3%) and male (36.7%), also age ranged 33-52 with mean 39±4.95; body mass index ranged 22,2±3.3 (kg/m 2 ), according to TLICS score (76.6%) had score 5, (3.3%) had score 6, (20.1%) had score 7; according to mechanism of injury (63.3%) falling from height, (13.3%) had motorcycle accident, (16.6%) had motor vehicle accident, (6,6%) had stuck a heavy object; according to fractured vertebra, (6,6%) had fracture T11, (20%) had fracture T12, (53.3%) had fracture L1, (20%) had fracture L2. Table (2) shows no statistically significant difference between groups according to age and gender data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table (1) shows that the female (63.3%) and male (36.7%), also age ranged 33-52 with mean 39±4.95; body mass index ranged 22,2±3.3 (kg/m 2 ), according to TLICS score (76.6%) had score 5, (3.3%) had score 6, (20.1%) had score 7; according to mechanism of injury (63.3%) falling from height, (13.3%) had motorcycle accident, (16.6%) had motor vehicle accident, (6,6%) had stuck a heavy object; according to fractured vertebra, (6,6%) had fracture T11, (20%) had fracture T12, (53.3%) had fracture L1, (20%) had fracture L2. Table (2) shows no statistically significant difference between groups according to age and gender data.…”
Section: Resultsmentioning
confidence: 99%
“…Thoracic and lumbar spine trauma (TLST) usually results from a high energy injury and is frequently associated with chest and abdominal injuries [1]. Mechanically unstable spinal injuries are commonly noted following severe spine trauma, and they often require surgical stabilization due to a high risk of neurological decline [2].…”
Section: Introductionmentioning
confidence: 99%
“…e potential thrombotic risk of intravenous application of TXA promoted the topical administration of TXA as a potentially safer and more targeted intraoperative hemostasis strategy [2]. Topical TXA has been widely used to reduce blood loss in orthopedic, cardiac, and thoracic surgery [26]. Topical TXA can provide direct and local high concentration drugs at the bleeding site and avoid the systemic exposure of TXA [1,2,27].…”
Section: Postoperative Aptt (Seconds)mentioning
confidence: 99%
“…Topical TXA can provide direct and local high concentration drugs at the bleeding site and avoid the systemic exposure of TXA [1,2,27]. Sudrasert et al [26] demonstrated that topical TXA could effectively decrease postoperative transfusion requirements and postoperative blood loss in patients undergoing long-segment instrumented posterior spinal fusion. A latest meta-analysis in 2018 showed that the topical administration of TXA in spine Total (95% CI) Heterogeneity: tau 2 = 0.02, chi 2 = 19.12, df = 5 (P = 0.002); I 2 = 74% Test for overall effect: Z = 0.57 (P = 0.57) Test for subgroup differences: chi 2 = 0.91, df = 1 (P = 0.34); I 2 = 0% surgery decreased TBL and drainage volume and reserved higher postoperative Hb level without increasing the risk of DVT, PE, or wound infection [1].…”
Section: Postoperative Aptt (Seconds)mentioning
confidence: 99%
“…Topical TXA has the advantage of direct and high local concentration at the bleeding site, and the risks associated with systemic administration are avoided. Although a few studies have looked at spine surgery [21][22][23], there is no consensus for its topical use in this field.…”
Section: Introductionmentioning
confidence: 99%